Television viewing and exposure to food-related commercials among European school children, associations with fruit and vegetable intake: a cross sectional study - Due Pernille; Rodrigo Carmen; de Bourdeaudhuij Ilse; Wind Marianne; Klepp Knut-Inge; Bjelland Mona; Brug Johannes (International Journal of Behavioral Nutrition and Physical Activity, 2007)
Abstract Background Fruit and vegetable intake is low among European children and exposure to TV is negatively associated with the intake of fruit and vegetables. The aim of the present study was to explore exposure to food commercials on TV in nine European countries. Associations between such exposure and intake of fruit and vegetables and possible mediating effects of attitudes toward and liking of fruit and vegetables were assessed. Methods A cross-sectional survey was performed in nine European countries, i.e. Austria, Belgium, Denmark, Iceland, the Netherlands, Norway, Portugal, Spain and Sweden, from October-December 2003, as a part of the Pro Children study. Data on usual intake of fruit and vegetables, and related correlates were collected by means of a self-administered questionnaire among 11-year-old school children (mean age 11.4 (sd = 0.48), 50.2% boys). Complete data was available for 13,035 children. Differences in exposure to TV ads between countries, gender and social class were explored by analysis of variance. Multiple linear regression analysis was used to test associations between exposure to TV ads and intake and to assess mediating effects. Results The large majority of children in all nine countries report recent exposure to a number of TV ads for food, and they were more often exposed to ads for unhealthy food than for fruit and vegetables (mean of 2.2 (sd = 1.0) unhealthy ads vs. mean of 1.7 (sd = 1.0) healthy ads; p < 0.001). Boys reported somewhat higher TV viewing than girls did (2.5 (sd = 1.7) vs. 2.2 (sd = 1.6) hours per day; p < 0.001), and children from lower social classes reported higher TV viewing than higher social class children did (2.4 (sd = 1.7) vs. 2.0 (sd = 1.5); p < 0.001). Across all countries, exposure to TV ads for healthy foods was positively associated (r = 0.09–0.16) with reported fruit and vegetable intake. This association was in part mediated by attitudes toward and liking of fruit and vegetables. Conclusion Exposure to TV ads for fruit and vegetables ...